A formative model for student nurse development and evaluation - A. S. van der Merwe; E. C. Roos; M. Mulder; A. Joubert; D. E. Botha (AOSIS, 1996)
Preparing student nurses for the profession is a complex task for nurse educators; especially when dealing with the development of personal and interpersonal skills, qualities and values held in high esteem by the nursing profession and the community they serve. These researchers developed a model for formative evaluation of students by using the principles of inductive and deductive reasoning. This model was implemented in clinical practice situations and evaluated for its usefulness. It seems that the model enhanced the standards of nursing care because it had a positive effect on the behaviour of students and they were better motivated; the model also improved interpersonal relationships and communication between practising nurses and students.